The Effects of protectionism on a small country the case of Uruguay - Connolly, Michael B. 1941- (Michael Bahaamonde); De Melo, Jaime (World Bank regional and sectoral studies, 1994)
"Competently executed series of studies on the distorted trade regime of Uruguay until the late 1980s and the effect of protectionism on a variety of economic outcomes. Topics covered range from the political economy of trade distortions to the sectoral impact of specific regulations. Worth reading"--Handbook of Latin American Studies, v. 57.